What about me ism insights from game theory, behavioral economics and moral philosophy - Hendricks, Vincent F. 1970- (Springer, 2025)
In this book, Vincent F. Hendricks draws on game theory, behavioral economics and moral philosophy in a scathing critique of what he calls whataboutmeism. A form of egoism in which life is viewed as a zero-sum game.The colleague is promoted; a friend hangs out with another friend but not you; and your partner decides to spend the day off with the friends. Promptly we may ask: "What about me?!" Often enough the answer to that recurring question should simply be: "What about you? It’s not about you!"By systematically confusing autonomy with egoism and groupthink with democracy we develop and sustain this way of thinking. To overcome this trend of whataboutmeism we must take a hard look at ourselves, the games we play, the way we behave and discipline ourselves into realizing ‘it’s not all about me’.Humorous, erudite yet scholarly, the book covers this prevalent trend in society that rages online as well as offline. By providing a full analysis of said trend based on game theory, behavioral economics and moral philosophy, the author helps us realise that it’s not all about me. It’s about us